2014
DOI: 10.1007/s10118-014-1545-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic degradation behaviors of poly(p-dioxanone) in ambient environments

Abstract: The effects of temperature and relative humidity on the hydrolytic degradation of poly(p-dioxanone) (PPDO) were investigated. The hydrolytic degradation behaviors were monitored by tracing the changes of water absorption, mechanical and crystalline properties, molecular weight and its distribution, surface morphologies, as well as infrared absorption peaks and hydrogen chemical shifts during the degradation. It is found that the water absorption increases whilst the intrinsic viscosity, tensile strength and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…After 4 weeks, the cracks of PPDO/6PDO become much wider although it just appears on the surface of PPDO. The cracks appear on the surface of PPDO degradation samples have also been reported previously . As we known, PDO in PPDO/PDO mixture can leach out of the mixtures and dissolve in the solution, and it can convert to monomer acid which can catalyze the hydrolysis during the degradation process further.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…After 4 weeks, the cracks of PPDO/6PDO become much wider although it just appears on the surface of PPDO. The cracks appear on the surface of PPDO degradation samples have also been reported previously . As we known, PDO in PPDO/PDO mixture can leach out of the mixtures and dissolve in the solution, and it can convert to monomer acid which can catalyze the hydrolysis during the degradation process further.…”
Section: Resultssupporting
confidence: 74%
“…Apparently, PPDO/PDO mixtures display a higher degradation rate. It has been reported that the temperature and relative humidity influence the hydrolytic degradation of PPDO . The increasing in crystallinity of PPDO is a consequence of the hydrolytic chain scission of unstable ester bonds and can be explained by the “cleavage‐induced crystallization” mechanism .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency toward hypercoagulability in the sheep model was noted, and the investigators also noted that the sheep anatomy provided a greater challenge than in humans for deployment, due to extreme bending of the introducer sheath imposed by the groin geometry. The rate of hydrolysis of the PPDO filament is directly dependent on temperature, and human blood temperatures are lower than ovine blood temperatures [ 39 ]. Therefore, bioconversion times in an ovine model are not representative of device opening times in vitro, and while X-rays were performed during the animal studies to understand the process of bioconversion, the data collected were not used to establish the time to opening of the device.…”
Section: Discussionmentioning
confidence: 99%